Single- vs Double-Decker Copper 12-MC-4 Metallacrown Using the Coordination Flexibility of a Soft Donor Ligand - Gamer, Christoph; Sundaresan, Sriram; Carrella, Luca M.; Rentschler, Eva (European Journal of Inorganic Chemistry, 2022)
2-Methylmercaptobenzohydroxamic acid (mmbHA) has been synthesized and used to form CuIICl2(MeOH)[12-MCCu(II)N(mmbHA)-4]2 ⋅ 4MeOH (1) and CuII(μ2-ClO4)(MeOH)2(py)4[12-MCCu(II)N(mmbHA)-4]ClO4 (2), a copper(II) based double-decker and a discrete metallacrown (MC) system, respectively. While 1 forms in the absence of a coordinating co-ligand, the presence of pyridine (Py) leads to a change in the coordination mode of mmbHA and a discrete MC 2 is formed. Both compounds have been structurally and magnetically characterized. The magnetic susceptibility measured from 2–300 K shows overall antiferromagnetic exchange coupling within both crown structures and the obtained coupling constants are J1=−88.0(1) cm−1and J2=−64.7(3) cm−1 for 1 and J1=−90.0(5) cm−1 and J2=−31.1(1) cm−1 for 2. However, the ratio of the coupling parameters is highly affected by the structural change.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Coordination Chemistry; Copper(II); Ion selectivity; Ligand; Metallacrown